Endoscopy-assisted high cervical anterolateral retropharyngeal approach to clivus: a cadaveric study - Cicek, Caner; Orhun, Ömer; Cevik, Orhun Mete; Rzayeva, Lala; Güdük, Mustafa; Usseli, Murat İmre; Aksoy, Mehmet Emin; Emel, Erhan; Pamir, M. Necmettin; Bozkurt, Baran (Frontiers in Surgery, 2024)
The surgical management of pathologies involving the clivus and craniocervical junction has always been considered a complex procedure because of the deeply located surgical targets and the surrounding complex neural and vascular anatomical structures. The most commonly used approaches to reach this area are transnasal, transoral, and transcervical approaches. We described a modified endoscope-assisted high cervical anterolateral retropharyngeal approach in which each stage of the procedure was demonstrated on human cadavers in a step-by-step manner using endoscopic camera views. This approach was performed unilaterally on 5 cadaver heads and bilaterally on 1 cadaver head. This approach was broken down into 9 steps. The neurovascular structures encountered at each step and their relationships with each other are demonstrated.